2001
DOI: 10.1080/00218460108029623
|View full text |Cite
|
Sign up to set email alerts
|

The Unified Lewis Acid - Base Approach to Adhesion and Solvation at the Liquid-Polymer Interface

Abstract: We present our unified Lewis acid-base approach to adhesion and solvation at the liquid-polymer interface. This approach is to complement the original methodologies proposed by Fowkes and by van Oss, Chaudhury and Good (VCG). Intermolecular interactions are primarily dominated by dispersion, d, hydrogen bonding, h, and secondarily affected by orientation, 0, and induction, i. Generally, the polarization component, p, represents both i and o interactions. Fowkes suggested that the acid-base component, yab, of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…There are limitations to the vOCG method when used for the prediction of interfacial energies. Several specific concerns raised are that the base components are systematically greater than the acid components, that experimentally determined surface energy components may depend on the set of fluids chosen for experiments, and that the values of the components may sometimes take negative values. , In response to the first concern, the relative magnitudes of the acid and base terms are set by the choice of the components of water, which are typically equal to each other but may be chosen to make typical acid and base values for other fluids comparable as shown by Della Volpe and Siboni. , The second concern may be addressed by choosing appropriate test fluids when characterizing the surface energy components, or by choosing many fluids. , The final concern is assuaged by noting that negative surface energy component values reported are often of a lesser magnitude than the error of the measurement. , Even with the concerns addressed, there may still be significant error in prediction of interfacial energy over a broad range of fluids as pointed out by Kwok and Lee. In addition, in the specific case of LIS, a subset of prior work has used ionic liquids as lubricants; unfortunately, not only are there very limited data on the acid–base components of these liquids, but the vOCG method would have trouble even with suitable data for pure ionic liquids due to the extent to which ionic liquids and water are mutually soluble, with water changing surface tension by nearly 50% in the presence of certain ionic liquids; therefore, ionic liquids are not considered in this analysis. , With these criticisms in mind, there is a wealth of literature on interfacial energy prediction, including data for the vOCG LW, acid, and base components for over 150 fluids and solids compiled in the Supporting Information along with measurements taken in this study, and the consensus is that the vOCG method is the most versatile choice for a broad range of fluids. ,,,,, Indeed, as demonstrated below, its predictive power is not only suitable for LIS, but it also offers additional insights that previously proposed design guidelines have not been able to properly capture.…”
Section: Predictive Lis Modelmentioning
confidence: 99%
“…There are limitations to the vOCG method when used for the prediction of interfacial energies. Several specific concerns raised are that the base components are systematically greater than the acid components, that experimentally determined surface energy components may depend on the set of fluids chosen for experiments, and that the values of the components may sometimes take negative values. , In response to the first concern, the relative magnitudes of the acid and base terms are set by the choice of the components of water, which are typically equal to each other but may be chosen to make typical acid and base values for other fluids comparable as shown by Della Volpe and Siboni. , The second concern may be addressed by choosing appropriate test fluids when characterizing the surface energy components, or by choosing many fluids. , The final concern is assuaged by noting that negative surface energy component values reported are often of a lesser magnitude than the error of the measurement. , Even with the concerns addressed, there may still be significant error in prediction of interfacial energy over a broad range of fluids as pointed out by Kwok and Lee. In addition, in the specific case of LIS, a subset of prior work has used ionic liquids as lubricants; unfortunately, not only are there very limited data on the acid–base components of these liquids, but the vOCG method would have trouble even with suitable data for pure ionic liquids due to the extent to which ionic liquids and water are mutually soluble, with water changing surface tension by nearly 50% in the presence of certain ionic liquids; therefore, ionic liquids are not considered in this analysis. , With these criticisms in mind, there is a wealth of literature on interfacial energy prediction, including data for the vOCG LW, acid, and base components for over 150 fluids and solids compiled in the Supporting Information along with measurements taken in this study, and the consensus is that the vOCG method is the most versatile choice for a broad range of fluids. ,,,,, Indeed, as demonstrated below, its predictive power is not only suitable for LIS, but it also offers additional insights that previously proposed design guidelines have not been able to properly capture.…”
Section: Predictive Lis Modelmentioning
confidence: 99%
“…In addition, it cannot be safely assumed that the characterisation of the solid surface is independent of the selection of the probe liquids 17–19. Lee20 derived a set of solvent data with more acidic parameters (more positive polar contributions) than the set of van Oss 8. He also accounted for the equilibrium spreading pressure even though van Oss21 asserts that this can be neglected when the surface free energy of the probe liquid is larger than that of the solid surface (γ L > γ S ).…”
Section: Theorymentioning
confidence: 99%
“…He also accounted for the equilibrium spreading pressure even though van Oss21 asserts that this can be neglected when the surface free energy of the probe liquid is larger than that of the solid surface (γ L > γ S ). Lee20 then found that a clean and vapor adsorption free Polyvinylchloride surface is acidic while it appears to be basic based on the acid–base components of van Oss 8. Still today there seems to be no reliable complete set of parameters 16.…”
Section: Theorymentioning
confidence: 99%
“…Understanding the molecular structures of these adhesives at interfaces is essential because interfacial structures dictate the physical performance of these interfaces. Thus it is necessary to understand interfacial structures to design interfaces with improved properties. ,, The molecular-level understanding of surfaces/interfaces involving polymers has been a challenge, as polymer surface structures and buried interfaces that include polymers are usually very complicated and difficult to examine in situ. In this paper, we use sum frequency generation (SFG) vibrational spectroscopy to investigate several buried polymer/silane interfaces.…”
Section: Introductionmentioning
confidence: 99%